Influence of sanitization on the physico-chemical and microbiological quality of organic and conventional broccoli - Lima, Giuseppina Pace Pereira; Machado, Tatiana Marquini [UNESP]; Furtado, Natalia Reis [UNESP]; Fleuri, Luciana Francisco [UNESP]; Vieira, Marizete Cavalcante de Souza [UNESP]; Oliveira, Luciana Manoel; Vianello, Fábio (My University, 2013)
The present study was carried out in order to evaluate the effect of chlorinated and ozonized water on the physico-chemical characteristics of broccoli, produced under organic and conventional cultivation procedures. Organic and conventional broccolis were subjected to two sanitation treatments, using chlorine and ozone, and were kept under cold storage for seven days. Analyses of pH, titrable acidity, soluble solids and weight loss were performed and the content of Cu, Mn and Zn was determined. In addition, the presence of pesticides was verified. The results show no influence of the cultivation method or the sanitation treatment on sample weight loss. Cultivation methods and sanitizing treatments affected broccoli pH, titratable acidity, and soluble solids during the evaluation period. No differences regarding the metal content on organic and conventional broccoli were observed. Furthermore, the presence of organochlorine compounds, nor other pesticides, was not detected both in organic and conventional vegetables.
Keywords: Brassica oleracea var. Italica; Pesticide residues; Titrable acidity; Soluble solids; pH; Metals; Ozone; Sanitation treatment.a